A Novel Rabies Vaccine Based on a Recombinant Bovine Herpes Virus Type 1 Expressing Rabies Virus Glycoprotein - Zhao, Caiquan; Gao, Jie; Wang, Yongzhi; Ji, Lina; Qin, Hui; Hu, Wei; Yang, Yang (Frontiers in Microbiology, 2022)
Rabies is a highly prevalent zoonotic disease and a public health threat worldwide. Currently licensed rabies vaccines are effective but less is known which would protect cattle. This study describes the construction of a novel recombinant bovine herpes virus type I (BHV-1) expressing rabies virus glycoprotein (RABV G) instead of its gE glycoprotein (gE) by CRISPR-Cas9 and homologous recombination technology (BHV-1-ΔgE-G). Insertion of the RABV G gene is stable after 20 rounds of in vitro passaging and the recombinant virus replicates to high titers in MDBK cells. The RABV G expresses in the recombinant virus-infected cells and on the virion surface of BHV-1-ΔgE-G. One single immunization with BHV-1-ΔgE-G-activated dendritic cells (DCs) and B cells furthermore induced a protective immune response in mice against severe lethal challenge infection. A protective level of RABV-specific virus-neutralizing antibody (VNA) was detected in intramuscular immunized mice and cattle without any clinical symptoms. This research demonstrated that the BHV-1 vector-based RABV vaccine is a potential candidate for cattle.